HUBUNGAN EXPLOSIVE POWER OTOT LENGAN BAHU DAN KOORDINASI MATA – TANGAN DENGAN HASIL SMASH PADA TIM BOLA VOLI PUTRA SMK TARUNA SATRIA PEKANBARU - Yudha Pratama; Drs. Saripin, M.Kes, AIFO '; Kristi Agust, S.Pd, M.Pd (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this study is still a lot of players who have experienced failure at the time did smash volleyball. This is allegedly due to its low explosive power arm muscles of shoulder and hand-eye coordination with the results of smash, This study was conducted to find out whether there is a relationship of the explosive power arm muscles of shoulder and hand-eye coordination with the results of smash in volleyball male team SMK Taruna Satria Pekan Baru. The sample in this study is the volleyball male team of SMK Taruna Satria Pekanbaru and amount 12 people. Sampling technique that is the overall population (total sampling). The instruments used in this research is a test used in measuring explosive power arm muscles of shoulder is by Two-Hand Medicine Ball Put, hand-eye coordination is a test that aims to measure the eye-hand coordination is someone with nerve center and Test the accuracy of the Smash as many as five balls of the test aims to measure the skills do a smash in the attack to the target quickly and directional. After that, the data is processed with statistics, to test normality test with lilifors on a significant extent of 0.05α. The hypothesis a relationship between Explosive Power shoulder arm muscles with the precision of the results smash, 2. There is a relationship between hand-eye coordination with the results accuracy smash, 3 There is a relationship between explosive power arm muscles of shoulder and hand-eye coordination with the results of smash. Based on the analysis of test lilifors produces Lcount (X1) of Ltable 0.242, 0.163 Lcount (X2) of Ltable 0.242 and 0.126 Lcount (Y) of Ltable 0.242, 0.219 means Lcount < Ltable, then the samples came from normal population. From the calculation of product moment correlation between explosive power shoulder arm muscles with the precision of the results smash X1 against Y is 0.643, hand-eye coordination with the results of smash X2 against Y is 0,808 and the explosive power arm muscles of shoulder and hand-eye coordination with the results of smash X1X2 against Y 0,873, where R aritmetic (0.873) > R table (0.632) therefore Ha is accepted and Ho is rejected. Thus there are relationship between the explosive power arm muscles of shoulder and hand-eye coordination with the results of smash in volleyball male team SMK Taruna Satria Pekanbaru.Key Words: Explosive Power Arm Muscles Of Shoulder And Hand-Eye Coordination With TheResults Of Smash In Volleyball